2016
DOI: 10.1515/acph-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization and dissolution studies of acyclovir solid dispersions with Pluronic F127 prepared by the kneading method

Abstract: The dissolution rate of anhydrous acyclovir was improved by the preparation of physical mixtures and solid dispersions with the non-ionic polymer Pluronic F127 using the kneading method at diff erent drug-to-polymer ratios. The obtained physical mixtures and solid dispersions were examined in terms of drug content and possible physical and chemical interactions between the drug and polymer using FTIR spectral studies, diff erential scanning calorimetry and powder X-ray diff raction analysis. The dissolution ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Therefore, new approaches in ACV formulation that improve its solubility and therapeutic efficacy are being investigated [6,7]. In this context, the use of polymeric micelles [8] or cyclodextrins [9][10][11] can be particularly suitable. Pluronic® F127 (Poloxamer 407, PF127), a poly(ethylene oxide) (PEO)− poly(propylene oxide) (PPO)− poly(ethylene oxide) (PEO) triblock, readily self-associates in aqueous medium forming micelle-like aggregates and even larger supramolecular structures leading to thermoreversible and mucoadhesive gels [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new approaches in ACV formulation that improve its solubility and therapeutic efficacy are being investigated [6,7]. In this context, the use of polymeric micelles [8] or cyclodextrins [9][10][11] can be particularly suitable. Pluronic® F127 (Poloxamer 407, PF127), a poly(ethylene oxide) (PEO)− poly(propylene oxide) (PPO)− poly(ethylene oxide) (PEO) triblock, readily self-associates in aqueous medium forming micelle-like aggregates and even larger supramolecular structures leading to thermoreversible and mucoadhesive gels [12].…”
Section: Introductionmentioning
confidence: 99%
“…Such study is valuable both in the academic and industrial contexts, as several liquid and semi-solid formulations of ACV are available on the market and significant differences in dissolution kinetics between polymorphs of ACV have been observed. 2,3 ACV form I slurried in MeOH (at aw £0.14), NNDMF and DMSO results in the formation of form II after one to four weeks (Figure 7), while slurrying in other 11 organic solvents did not result in a phase change (see Scheme 1A, and ESI Figures S26-27). Slurrying of form I in DMSO resulted in the formation of an opaque gel-like material, containing highly crystalline form II (Figure 8 and Figure 9).…”
Section: Solution-mediated Phase Transformation Of Acv Forms V and Itmentioning
confidence: 99%
“…1 This is in line with its limited bioavailability (5 to 30%), which varies between individuals. 2 Furthermore, it is known that different ACV solid forms display substantial differences in dissolution kinetics, which may affect the bioavailability of the drug. 2,3 ACV can form varied hydrogen bonding networks due to the presence of eight potential hydrogen donors/acceptors and a flexible side chain, which results in four polymorphs and two hydrate forms reported to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerosol is a fine particles suspension or liquid drops in a gas, which can diffuse independently of breathing behaviour, and allow diseases treatment of the upper and lower airways (which share their pathogenic mechanisms) and which frequently they occur simultaneously as -united airway disease‖ [28] . The efficacy of this method is related to the size of the dispersed substance, preferably less than 10 µm, which allows good penetration into the bronchial tree and causes a high local concentration of a substance [32] . The most important practical advantage of this method is its simplicity and very low probability of adverse events as observed in a meta-analysis study where safety data was reviewed in 24 trials: 13 trials (1,363 neonates, 703 treated with hypertonic saline) reported no adverse event, and 11 trials (2,360 infants, 1,265 treated with hypertonic saline) reported at least one adverse event, most of which were mild and resolved spontaneously [29] .…”
Section: Introductionmentioning
confidence: 99%